2013
DOI: 10.1007/s11657-013-0151-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effect of dietary calcium intake and 25 OHD status on bone turnover in women in Pakistan

Abstract: Compromised bone health is seen in community-dwelling females of Karachi. There is a need to perform large-scale community-based studies in all age groups to understand the interplay of markers in our population to understand the impact of these variables translating into the risk of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…Our finding of very high prevalence of inadequate vitamin D status is in keeping with those of other investigators, who have reported a low prevalence of optimal vitamin D status among women in Karachi, Pakistan, where one study has reported that 84 % of participants had serum 25(OH)D concentrations <75 nmol/L [ 12 ]; another has reported that 91 % of participants had serum concentrations <50 nmol/L [ 1 ]. Studies conducted elsewhere in Asia have reported similarly high rates of vitamin D deficiency among women [ 13 – 15 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding of very high prevalence of inadequate vitamin D status is in keeping with those of other investigators, who have reported a low prevalence of optimal vitamin D status among women in Karachi, Pakistan, where one study has reported that 84 % of participants had serum 25(OH)D concentrations <75 nmol/L [ 12 ]; another has reported that 91 % of participants had serum concentrations <50 nmol/L [ 1 ]. Studies conducted elsewhere in Asia have reported similarly high rates of vitamin D deficiency among women [ 13 – 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Despite its sub-tropical location and sunny climate, vitamin D deficiency has been reported to be very common in Pakistan, especially among women: a recent study reported that 90 % of pre-menopausal females had serum 25-hydroxyvitamin D (25[OH] D) concentrations <50 nmol/L (20 ng/mL) [ 1 ]. A growing literature points to the importance of adequate maternal vitamin D status in protecting against a wide range of adverse obstetric and neonatal outcomes, including pre-term birth, fetal neurodevelopment and neonatal infection [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found a vast majority of pregnant women (96.3%) were de cient in vitamin D at enrolment. The prevalence of vitamin D de ciency observed is alarming and the ndings in our study are similar to other studies conducted in Karachi, Pakistan, which reported de ciency in over 90% females (Anwar et al, 2016;A. Khan et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, a trial from Pakistan reported vitamin D de ciency in 90.5% women (A. Khan, Naureen, Iqbal, & Dar, 2013). The most recent National Nutrition Survey (NNS) 2018 reported a prevalence of vitamin D de ciency in 79.7% Women of Reproductive Age (WRA), which has increased by 11-13% since the previous NNS (2011) (Government of Pakistan, 2013; Government of Pakistan & UNICEF, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation